Preliminary Reference Interval Estimation for Hemolymph Analysis in Free‐Ranging Mangrove Horseshoe Crab ( Carcinoscorpius rotundicauda ) - Farsia Naher; Md. Nayeem Hossain; Md Ridoan Pasha; Akbar John; Sk. Ahmad Al Nahid (Veterinary Clinical Pathology, 2026)
ABSTRACT Background The mangrove horseshoe crab ( Carcinoscorpius rotundicauda ), a species thriving in the muddy brackish waters of Cox's Bazar, holds significant ecological and biomedical value. Hematological and biochemical analyses can serve as a valuable diagnostic tool for assessing health; however, reports remain limited for horseshoe crabs. Objective This study investigated hemolymph values to determine preliminary reference intervals (RIs) from free‐ranging mangrove horseshoe crabs. Methods Forty adult Carcinoscorpius rotundicauda (20 males, 20 females) were collected from intertidal zones of Cox's Bazar in February 2024. Hemolymph was extracted by cardiac puncture under cold anesthesia for amebocyte counting and biochemical profiling. Plasma metabolites, enzymes, and electrolytes were analyzed using a standard automated laboratory biochemistry analyzer (Humalyzer 3000, Human Diagnostics, Germany), and data were statistically evaluated in accordance with established guidelines. Results Total amoebocyte counts demonstrated substantial variability (RI: 0.6–38.5 × 10 6 cells/mL). This study found significantly ( p < 0.05) higher levels of cholesterol, triglycerides, chloride (Cl − ), calcium (Ca 2+ ), magnesium (Mg 2+ ), and aspartate aminotransferase (AST) in female horseshoe crabs, whereas alanine aminotransferase (ALT) activity was significantly higher in males. In contrast, no significant ( p > 0.05) differences between sexes were observed in glucose, total protein, albumin, alkaline phosphatase (ALP), uric acid, creatinine, urea, blood urea nitrogen (BUN), sodium (Na + ), potassium (K + ), and amebocyte counts. Reference intervals (RIs) were established after excluding outliers identified across multiple measurands in both sexes. Conclusion This study provides baseline data and underscores the need for further research, particularly across different seasons, to enhance the suitability and applicability of the established RIs.